Inhibicija proteinov toplotnega šoka 90 - Gradišek, Nina (Placebo, 2023)
Hsp90 is one of the most important chaperones involved in regulation of cell homeostasis and in the maturation and folding of several proteins, many of which are associated with progress of cancer and other, mostly neurodegenerative, diseases. Its inhibition presents a promising target in cancer with the option of combinatorial attack on numerous oncogenic pathways. Clinical Hsp90 inhibitors bind to N-terminal ATP-binding pockets, suppressing ATPase activity and exhibiting pan-inhibitory activity. Adverse effects of said inhibition that include heat shock response lead to the development of new strategies for Hsp90 inhibition. Novel Hsp90 inhibitors offer selective suppression of Hsp90 isoforms or specific disruption of Hsp90-co-chaperone protein-protein interaction, C-terminal domain inhibition and inhibition of Hsp90 post-translational modifications. While they have yet to enter clinical trials their results from preclinical stages show a great potential for future research of Hsp90 inhibitors.
Keywords: Hsp90; izofomno selektivni inhibitorji; Nevrodegenerativne bolezni; pan-inhibicija; selektivni inhibitorji